MANUFACTURING OF AUTOMOTIVE PARTS FROM COMPOSITE MATERIALS: RESOURCE SHORTAGES, TECHNOLOGICAL PROCESSES, AND INNOVATIVE SOLUTIONS - Tadjikuziyev Rakhmatjan Makhamadovich (Web of Journals Publishing, 2025)
This article explores the technological aspects of manufacturing automotive parts and equipment components from composite materials, which are widely used in the modern automotive industry. A significant issue highlighted in the study is the shortage of materials during the production, maintenance, repair, or replacement of these parts. The paper emphasizes the importance of addressing this problem for national industrial sectors and outlines technological processes aimed at efficiently utilizing residual resources. Furthermore, it presents new models and methods for the rapid production of composite-assembled compounds. The study provides insights into innovative approaches that can ensure timely and cost-effective manufacturing, thereby enhancing the sustainability and efficiency of automotive production.
Keywords: Resources, composite compounds, plastic, alloy, blanks, planks, mold, stamp, press, forging, punch, die, non-metal, steel, non-ferrous metal, alloys, elements, residuals, mechanical engineering, physical, chemical, mechanical, mechanisms, instruments, machinery, equipment, hydraulic, pneumatic, operation, technique, technology, shape, assembly, welding, cutting.